Extreme space-weather effect on D-region ionosphere in Indian low latitude region - Venkatesham, K.; Singh, Rajesh (My University, 2018)
The present study delineates on the observations and modelling of low latitude D-region ionosphere perturbations caused by strongest solar flare (X6.9) of solar cycle 24. An extreme space weather event occurred on 9 August 2011. To understand the severity of X-class flare on ionosphere, a comparative study was made with a low intensity C-class flare of 6 August 2011. Both flares originated from the same sunspot AR#1263. Very low frequency (VLF) waves propagating in the Earth’s ionosphere wave guide (EIWG) measured from VLF transmitter NWC (19.8 kHz) located in Australia, and recorded at Allahabad (India) were used. The recorded VLF amplitude and phase were modelled with long wavelength propagation capability code to understand solar flare-induced ionospheric variation. Modelling results revealed that the lower boundary of D-region ionosphere is lowered by 10 km during X-class and 1.0 km for C-class flare. This implies change in the properties of EIWG, and hence becomes important to observe our ionosphere on continuous basis for space weather events since ionosphere is the key medium of propagation for radio waves.
Keywords: Low latitude; D-region ionosphere; Solar flare; Solar cycle 24; Very low frequency waves